Evaluation of electrical nerve stimulation to confirm sacrococcygeal epidural needle placement in dogs. (July 2021) - Verdier, Natali; Martinez-Taboada, Fernando; Otero, Pablo E.; Redondo García, José Ignacio; Zaccagnini, Andrea S.; Costoya, Alejo A.; Tarragona, Lisa; Portela, Diego A.
Abstract: Objectives: To evaluate the use of 0.7 mA as a fixed electrical current to indicate epidural needle placement and to confirm that 0.7 mA is greater than the upper limit of the minimal electrical threshold (MET) for sacrococcygeal epidural needle placement in dogs. Study design: Prospective clinical study. Animals: A group of 20 client-owned dogs. Methods: During general anesthesia and with standard monitoring, the presence of the patellar reflex was confirmed in all dogs. An insulated needle was inserted through the sacrococcygeal intervertebral junction, and absence of tail movement was confirmed when a fixed electrical current of 0.7 mA was applied. Then, the needle was further advanced toward the epidural space until the expected motor response was obtained – the nerve stimulation test (NST). The NST was considered positive when a motor response of the muscles of the tail was elicited but not the perineal muscles, whereas it was considered negative when no movement of the tail was evoked. The electrical current was turned to 0 mA and then increased by 0.01 mA increments until tail movement was evoked; this was recorded as the MET. In the positive NST cases, 0.05 mL cm –1 occipitococcygeal length of 2% lidocaine or 0.25–0.5% bupivacaine was administered. Epidural blockade was confirmed by the loss of patellar reflex. Descriptive statistics were used to present data. Results: Sacrococcygeal epidural needle placement, corroborated by loss of the patellar reflex, was correctly predicted in 89.5% (95% confidence interval, 68.6–97.1%) of the cases. The MET was 0.22 mA (0.11–0.36). Conclusions and clinical relevance: A current of 0.7 mA is approximately twice the upper limit of the MET for epidural placement. Therefore, this study demonstrates, with a success rate of 89.5%, the adequacy of using 0.7 mA as the fixed electrical current to detect sacrococcygeal epidural needle placement in dogs.